FFAer wins award (Raton, New Mexico Raton Range, 1988)
Article on Elizabeth Morgan being designated as the most outstanding volunteer in the nation by the Future Farmers of America.
Master list item #:33
File location is in the Raton File Cabinet
Keywords: Morgan, Elizabeth; Domenici, Pete; Lang, Richard; Dobesh, Amy; Future Farmers of America; FFA Building Our American Communities program; RJ Nabisco Company; Kennedy Center; Local History; Biography; Award; Volunteers; Community; Community Projects; Raton, New Mexico; Washington, D.C.; Wisconsin